COMBINED TREATMENT FOR EARLY-STAGE SKIN CANCER OF THE HEAD AND NECK AREA - A.A. Ganiev; Sh. Yu. Abdullaev; S.Z. Abdurahmonov (Scholar Express Journals, 2021)
This article presents the results of a study of 140 patients with skin cancer of the scalp of the neck. According to the clinical data obtained, heating the malignant tumor cells immediately before the radiation exposure activates the cancer cells, which in turn enhances their damage during the subsequent irradiation, increasing the effectiveness of treatment. The authors recommend the use of the developed tactical approaches to the treatment of skin cancer patients in the head and neck region using a combined method will allow to achieve optimal immediate, long-term, aesthetic and functional results, which will ensure the full rehabilitation of patients after treatment.
Keywords: Near-focus X-ray therapy; skin cancer; hyperthermia